LECTURERS’ ENGAGEMENT OF OPEN SOURCE SOFTWARE (OSS) FOR LEARNING IN UNIVERSITY OF ILORIN, ILORIN, NIGERIA - Ayotunde Atanda Falade; Moridiyah Omolola Ibrahim; Olubunmi Michael Odewumi (Sanata Dharma University Yogyakarta, 2021)
The growth and development of education is associated primarily with the use of ICT, whereas, the evolution of the Information and Communication Technology (ICT) gives birth to Open Source Software (OSS), a product of instructional delivery. The research was of descriptive research of the survey type and the population for the study consisted of 300 with 125 male and 175 female lecturers in university of Ilorin, Ilorin, Nigeria. The research instrument was researchers’ designed questionnaire titled lecturers perceived ease of use of Open Source Software. The validation of the instrument was done by researchers’ colleagues and two lecturers in faculty of education, University of Ibadan. While, the reliability, was pilot-tested on 20 lecturers at the Obafemi Awolowo University, Ile – Ife, Nigeria with Cronbach’s Alpha and the values were 0.73 and 0.67 respectively, the instruments were randomly given to the lecturers, and the data obtained were analysed using the descriptive and inferential statistics. Findings revealed that lecturers were positive on the use of the OSS and it was recommended that there should be continued use open source for learning.